Delivery of cancer care in Sri Lanka. (December 2018) - Gunasekera, Sanjeeva; Seneviratne, Sanjeewa; Wijeratne, Thiwanka; Booth, Christopher M.
Abstract: Sri Lanka, a small island nation in South Asia, is in the process of transition from a low-middle to an upper middle income country. With these changes, the burden of non-communicable disease has increased significantly. Cancer incidence has nearly doubled in twenty-five years. The pattern of cancer is also changing with breast, lung and colorectal cancers showing marked increased incidence compared to traditionally common cancers of the oral cavity/oropharynx and cervix. Public sector cancer care is free of charge in Sri Lanka and is delivered through 19 regional centres covering all 9 provinces. The National Cancer Institute, Sri Lanka is the country's nodal cancer center and the only dedicated cancer hospital. The Post Graduate Institute of Medicine, University of Colombo conducts training programs in clinical oncology with recent training programs now underway in paediatric oncology and haemato-oncology. The National Cancer Control Program has maintained the Sri Lanka Cancer Registry since 1985. Availability of universal free health care, accessible regional cancer treatment units, and a national oncology training program are strengths of the Sri Lankan cancer system. However the system faces many challenges including: lack of a formal Health Technology Assessment process, inadequate radiation therapy facilities, migration of oncologists to high-income countries, lack of a formal palliative care service, and very limited research capacity.